Mechanical Performance Evaluation Of Improved Soils Using Compound Stabilizer And Fibre Reinforcement - Bagheri, Younes (2014)
Construction of civil engineering structures on weak or soft soil is difficult without any soil improvement due to their poor shear strength and high compressibility. The problems of utilization of common stabilizers are such as: high cost of production, increment in greenhouse gases emissions followed by the cement and lime production and application on only a certain type of soils. In this study, effectiveness of CLR (Cement-Lime-Rice husk ash admixture), CL (Cement-Lime admixture), OPEFB fibre (Oil Palm Empty Fruit Bunch) and OPEFB-CLR on geotechnical properties of problematic soils was evaluated and investigated. The primary objective of this research was to study the strength, deformation and compaction characteristics of CLR treated soils and fibre-CLR treated soils as a reinforced material on weak, soft or problematic soils. This was achieved by studying the changes induced in treated and untreated soils using grain size distribution, atterberg limits, compaction ability (standard proctor test), oedometer, california bearing ratio (CBR), unconfined compressive strength and consolidatedundrained triaxial (CU). To evaluate the effects of random distribution of OPEFB coated fibres on treated soil a series of triaxial CU test were carried out. The fibres coated with Acrylonitrile Butadiene Styrene (ABS) provide acceptable protection against the biodegradability of the OPEFB fibre. In addition, CU triaxial test was also conducted to evaluate the influence of optimum OPEFB coated fibre on the stress– strain–strength behaviour of treated soil with 10% and 12.5% CLR contents at 7 and 28 days of curing.